2000
DOI: 10.1046/j.1365-4362.2000.00990.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of endemic outbreaks of scabies with allethrin, permethrin, and ivermectin

Abstract: Outbreaks of scabies in populations of elderly people require special management for disease control. Synchronous treatment with external permethrin cream 5% or allethrin spray, including all IOP once, and close control offers a time-saving, cheap, and reliable method. Crusted scabies should be treated by oral administration of ivermectin once or twice after an interval of 8 days. Additional applications of permethrin and mechanical clearing of hyperkeratotic subungual areas shorten the course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 31 publications
0
39
0
2
Order By: Relevance
“…Several clinical studies have shown that permethin achieves higher clearance rates than lindane and crotomiton. 28 Mass treatment with permethrin has also been effective in controlling scabies in communities in which it is endemic.…”
Section: Permethrinmentioning
confidence: 99%
“…Several clinical studies have shown that permethin achieves higher clearance rates than lindane and crotomiton. 28 Mass treatment with permethrin has also been effective in controlling scabies in communities in which it is endemic.…”
Section: Permethrinmentioning
confidence: 99%
“…Although large studies showed that permethrin had low toxicity in mammals, active permethrin could not be detected in blood and urine in some studies conducted on volunteers. This drug was reported to be used also in rosacea depending on the results of the studies on facial demodicidosis and diseases associated with other mites [9, 10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that permethrin has a higher clearance rate than lindane and crotamiton. 28 The limiting factor in the use of permethrin is its cost as it is the most expensive of all the topical scabicides. 4 The various topical antiscabietic agents and their side effects are summarised in table 2.…”
Section: Malathionmentioning
confidence: 99%